Peran Amanat Agung Terhadap Penyembah Watu Pinawetengan - Taogan, Frischo Ridhoi; Suseno, Aji; Arifianto, Yonatan Alex (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2022)
Minahasa is one of the ethnic groups in North Sulawesi. Christians are the majority in the area. Along with the development of Christianity in Minahasa, it did not make the indigenous religious culture erased. One of the concerns is the ritual carried out at Watu Pinawetengan called "Kampetan". The ritual has a high appeal, because the ceremony is carried out by means of prayer, reading the Bible, there is a dance and the climax is where the ritual leader or ritual participant is possessed by ancestral spirits and speaks in the original Minahasa language, and someone else translates. The purpose of this ritual is the preservation of local culture, but the other purpose of the participants is to respect/worship and ask for protection to the ancestors. So in the ritual they wait for instructions from their ancestors to be obeyed and hope for healing in the ritual. Therefore, the church must be responsible for designing the structure of evangelism to them. The role of the church through the great mandate of Jesus Christ must be seen in this case. Therefore, the author uses a theological research method with a literature study model and examines Bible verses with the Hermeneutic Word Study model in Matthew 28:19-20 so that research results are obtained based on an analysis of existing data that the church must play a role through the role of the Great Commission in ministry to worshipers at Watu Pinawetengan yang inclined towards animism and syncretism. Worshiping ancestors is an act that violates God's law. Minahasa merupakan salah satu etnis di Sulawesi utara.  Pemeluk agama Kristen merupakan kaum mayoritas di daerah tersebut.  Seiring dengan perkembangan kekristenan di Minahasa, ternyata tidak membuat budaya agama pribumi terhapus.  Salah satu yang menjadi perhatian adalah ritual yang dilaksanakan di Watu Pinawetengan yang disebut “Kampetan”.  Ritual tersebut mempunyai daya tarik yang tinggi, karena upacara yang dilakukan dilaksanakan dengan cara berdoa, membaca alkitab, ada tarian dan puncaknya adalah dimana pemimpin ritual atau peserta ritual ada yang dirasuki roh leluhur dan berbicara dalam bahasa asli Minahasa, serta seorang yang lain menerjemahkan.  Tujuan ritual ini adalah pelestarian budaya lokal, tetapi tujuan lainnya dari para peserta adalah sebagai penghormatan/ penyembahan serta memohon perlindungan kepada leluhur.  Sehingga dalam ritual tersebut mereka menantikan instruksi-instruksi dari leluhur untuk ditaati dan berharap kesembuhan dalam ritual tersebut.  Oleh sebab itu, gereja harus bertanggung jawab untuk merancang bangun pewartaan injil kepada mereka.  Peran gereja melalui mandat agung Yesus Kristus harus terlihat dalam kasus ini.  Oleh sebab itu, penulis menggunakan metode penelitian teologis dengan model studi pustaka dan mengkaji ayat Alkitab dengan model Hermeneutika Studi Kata dalam nats Matius 28:19-20 sehingga diperolehlah hasil riset berdasarkan Analisa data yang ada bahwasannya gereja harus berperan melalui peran Amanat Agung dalam pelayanan terhadap penyembah di Watu Pinawetengan yang cenderung ke animisme dan sinkritisme.  Penyembahan kepada leluhur merupakan tindakan yang menyalahi hukum Allah.